Endothelium and Its Alterations in Cardiovascular Diseases: Life Style Intervention. (26th February 2014) - Favero, Gaia; Paganelli, Corrado; Buffoli, Barbara; Rodella, Luigi Fabrizio; Rezzani, Rita
Abstract : The endothelium, which forms the inner cellular lining of blood vessels and lymphatics, is a highly metabolically active organ that is involved in many physiopathological processes, including the control of vasomotor tone, barrier function, leukocyte adhesion, and trafficking and inflammation. In this review, we summarized and described the following: (i) endothelial cell function in physiological conditions and (ii) endothelial cell activation and dysfunction in the main cardiovascular diseases (such as atherosclerosis, and hypertension) and to diabetes, cigarette smoking, and aging physiological process. Finally, we presented the currently available evidence that supports the beneficial effects of physical activity and various dietary compounds on endothelial functions.